2006
DOI: 10.1207/s15327922par0604_1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Depression and Parenting: Implications for Children's Emergent Emotion Regulation and Behavioral Functioning

Abstract: SYNOPSISObjective. We investigated the role of mothers' elevated depressive symptoms on scaffolding and availability to assist preschool children's regulatory development. Design. A sample of 208 3-year-olds and their mothers was drawn from an ongoing longitudinal study and followed to child age 4. Maternal scaffolding behaviors and children's emotion regulation competencies were assessed using behavioral coding schemes applied to observations of structured laboratory tasks, and maternal depressive symptoms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
248
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(263 citation statements)
references
References 51 publications
10
248
1
4
Order By: Relevance
“…For example, one study by Suveg et al [22] found that in comparison to mothers of children without anxiety disorders, mothers of children with anxiety disorders, who also had higher rates of psychopathology symptoms, used fewer emotion words and were more likely to discourage emotion-related discussion, and reported restricted family expressiveness. The lack of parent coaching of emotional experiences may contribute to emotion dysregulation and indeed, parental psychopathology has been identified as a risk factor for child emotion dysregulation [23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study by Suveg et al [22] found that in comparison to mothers of children without anxiety disorders, mothers of children with anxiety disorders, who also had higher rates of psychopathology symptoms, used fewer emotion words and were more likely to discourage emotion-related discussion, and reported restricted family expressiveness. The lack of parent coaching of emotional experiences may contribute to emotion dysregulation and indeed, parental psychopathology has been identified as a risk factor for child emotion dysregulation [23].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal depression may increase child psychopathology through its association with less parental warmth and increased parental hostility (Bor and Sanders 2004), as well as poorer maternal scaffolding ability, i.e., ability to provide structure in frustrating situations (Hoffman et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Parenting There is consistent evidence that parental hostility (Heller and Baker 2000), warmth (Hipwell et al 2008) and scaffolding (Hoffman et al 2006) are associated with externalizing behaviors and ODD symptoms. Scaffolding is a parenting skill that involves providing parental support to help the child achieve a level of competence on a task, and then withdrawing the no-longer-needed support (Hoffman et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many researchers have extensively studied the relationship between maternal depression and preschool children's poor functioning in emotional, behavioural, and cognitive aspects. Compared to the children of non-depressed mothers, the children of depressed mothers show poor regulation of emotion and emotional expression (Hoffman et al, 2006;Hooper et al, 2015), as well as higher rates of both externalising (e.g. hyperactivity and aggressive behaviour) and internalising problem behaviours (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…However, maternal depression and children's hot EF might be related, given the fact that both contain emotional elements. Furthermore, there has been considerable research which sought to identify the impacts of maternal depression on children's emotional regulation and expression (Hoffman, et al, 2006;Hooper et al, 2015), one of the functions controlled by the hot EF.…”
Section: Introductionmentioning
confidence: 99%